Pharmacological Evaluation of Newly Synthesized Cannabidiol Derivates on H9c2 Cells - Kitti Szőke; Richárd Kajtár; Alexandra Gyöngyösi; Attila Czompa; Adina Fésüs; Eszter Boglárka Lőrincz; Ferenc Dániel Petróczi; Pál Herczegh; István Bak; Anikó Borbás; Ilona Bereczki; István Lekli (MDPI AG, 2023)
Cannabidiol (CBD) is a nonpsychoactive phytocannabinoid that can be found in Cannabis sativa and possesses numerous pharmacological effects. Due to these promising effects, CBD can be used in a wide variety of diseases, for instance cardiovascular diseases. However, CBD, like tetrahydrocannabinol (THC), has low bioavailability, poor water solubility, and a variable pharmacokinetic profile, which hinders its therapeutic use. Chemical derivatization of CBD offers us potential ways to overcome these issues. We prepared three new CBD derivatives substituted on the aromatic ring by Mannich-type reactions, which have not been described so far for the modification of cannabinoids, and studied the protective effect they have on cardiomyocytes exposed to oxidative stress and hypoxia/reoxygenation (H/R) compared to the parent compound. An MTT assay was performed to determine the viability of rat cardiomyocytes treated with test compounds. Trypan blue exclusion and lactate dehydrogenase (LDH) release assays were carried out to study the effect of the new compounds in cells exposed to H2O2 or hypoxia/reoxygenation (H/R). Direct antioxidant activity was evaluated by a total antioxidant capacity (TAC) assay. To study antioxidant protein levels, HO-1, SOD, catalase, and Western blot analysis were carried out. pIC50 (the negative log of the IC50) values were as follows: CBD1: 4.113, CBD2: 3.995, CBD3: 4.190, and CBD: 4.671. The newly synthesized CBD derivatives prevented cell death induced by H/R, especially CBD2. CBD has the largest direct antioxidant activity. The levels of antioxidant proteins were increased differently after pretreatment with synthetic CBD derivatives and CBD. Taken together, our newly synthesized CBD derivatives are able to decrease cytotoxicity during oxidative stress and H/R. The compounds have similar or better effects than CBD on H9c2 cells.